Perceived tranquility in green urban open spaces. Issue 3 (3rd July 2018) - Marafa, Lawal M.; Tsang, Felix; Watts, Greg; Yuan, Xiao-mei
ABSTRACT: Tranquility has a number of facets. Given the role that tranquility plays in societies, it is increasingly seen as an environmental indicator. Earlier, some have identified tranquility as contributing to health and wellbeing of individuals and the society, making it to be rooted in the context of sound natural ecosystems as a desirable environmental characteristic. Previous studies have identified tranquility places as having links to nature and natural features, wild landscapes, naturally behaving wildlife and natural sounds. The question of how tranquility can be evaluated and the perception of tranquility by visitors is a continuous recurrence. This study therefore selected seven green open spaces in Hong Kong in an attempt to answer these and other questions that are arising. Although results vary, it however provides a perspective on how people perceive tranquil spaces as part of their leisure and recreation indulgence, given rise to the concept of eco-leisure.